DECONSTRUCTING TRADEMARK AUTHENTICITY: A COMPARATIVE STUDY OF LEGAL INTERPRETATIONS IN INDONESIA, OMAN, AND THE PHILIPPINES - I Gede Agus Kurniawan; Ni Made Dyah Sukasmini Merthada; I Made Wirya Darma; Ni Gusti Agung Ayu Mas Tri Wulandari; Souad Ahmed Ezzerouali; Princess Alyssa Tee-anastacio (Diponegoro Law Review, 2025)
This study examines the concept of trademark authenticity in Indonesia, Oman, and the Philippines through Jacques Derrida’s deconstruction theory. In trademark law, authenticity is commonly perceived as a stable attribute of a product and its origin. However, this notion is contested by the varying ways national legal systems apply trademark law. In this pluralistic context, authenticity is not a fixed legal fact but a matter of interpretation. By employing Derrida's theory, this research investigates how the meaning of authenticity is constructed, destabilized, and reconstructed across different intellectual property frameworks. It also explores how each country's legal system addresses or resists the inherent instability of trademark meanings. Using a comparative legal analysis, doctrinal research, and a post-structuralist interpretive approach, the study finds that in Indonesia, authenticity is closely tied to consumer perception; in Oman, it is linked to origin and moral identity; and in the Philippines, fairness and commercial honesty play a significant role. The novelty of this research lies in its assertion that brand authenticity is a legal construct subject to reinterpretation, challenging the notion of fixed legal definitions. The findings urge a reconsideration of national intellectual property systems, advocating for a more flexible, culturally situated view of brands that accommodates the evolving global context. This study also reveals that the legal understanding of trademark authenticity in these jurisdictions is shaped by a logocentric and hierarchical legal structure, opening space for critique of the dominance of a single legal narrative over diverse social realities. A limitation of this study is its reliance on conceptual analysis without empirical data, suggesting the need for further research through case studies to strengthen the findings.